Construction of training process of tennis players aged 5-6 years, taking into account the specifics of the development and control of their coordination skills - Kozak, A. M.; Ibraimova, M. V. (Physical Education of Students, 2014)
Purpose: Presented results of the research to determine the features of the construction of the training process for young tennis players aged 5-6 years, in particular the specific application of pedagogical testing to test the level of development of their coordination skills. Material: The survey was attended by 30 experts. Results: Established that bigger part of coaches build the training process at the initial stage of preparation on the basis of the game approach and apply a program of the International Tennis Federation "Play and stay". About two-thirds of the coaches do not carry out a selection of tennis players aged 5-6 or make it only in individual cases. To assess the level of development of motor abilities are equally important coaches define pedagogical supervision and pedagogical testing. A significant proportion of respondents (43%) previously had experience in assessing motor abilities of tennis players 5-6 years by mean of pedagogical tests. Conclusions: Overwhelming majority of coaches support the idea of having to modify the tests in accordance with the age characterristics of tennis players aged 5-6 years and expediency of complex assessment of the level of development of their coordination skills.